Application of Appropriate Technology Purification Oil Based on Cocoa Bark (Theobroma cacao L.) As Bio-Adsorbent for Purification of Used Cooking Oil in Kedaton Plantation, Panti Village - Hakiki, Rizki Maulana; Tiana Febrianti Eka Prasetyani; Rossi Agnessi Pebriana; Amelia Permata Ayunda; Syeikh Maulana Bima Suci; Amellyah Isna Ainaiyah; Mutiara Rengganis Nurul Putri Azhari; Isni Salma Salsabillah; Sekar Jasmin Azzahra; Nico Dimas Saputro; Istiqomah Rahmawati (Jurnal Inovasi Sains dan Teknologi untuk Masyarakat, 2024)
Using cooking oil repeatedly will have an impact on health. Cooking oil repeatedly changes color to a darker color, produces an unpleasant odor, and has high levels of fatty acids. Cooking oil experiences changes due to the chemical properties of cooking oil, such as a reaction where the color changes to brown when cooking oil is used at high temperatures by reacting with air. Therefore, it is necessary to purify used cooking oil to be used as a material that is more beneficial to society. The utilization of cocoa shell waste into carbon that has been processed is used for the adsorption process of purification of used cooking oil. The process of purifying used cooking oil begins with making activated charcoal, chemical activation of activated charcoal with hydrochloric acid (HCl), assembling appropriate technology for oil purification, adsorption process of used cooking oil which goes through several stages of purification, namely zeolite stone, cotton, cocoa charcoal, cotton and filter cloth. , and the process of using purified used cooking oil into aromatherapy candles. The materials used in making candles are paraffin and used cooking oil in a 1:1 ratio. Candles are packaged attractively to provide consumers and add selling value. This activity attracted the enthusiasm of the community to utilize used cooking oil into aroma therapy candles. In addition, the Panti Village Tourism Awareness Group is interested in utilizing used cooking oil to make souvenir aroma therapy candles at Panti village tourist attractions.It is hoped that using used cooking oil that has been purified into aromatherapy candles will become a source of income for the people of Kedaton Plantation, reducing waste disposal so that the environment will be better protected.